Composition and function of the microbial community related with the nitrogen cycling on the potato rhizosphere (2013)
In the S. tuberosum group phureja crops, mineral fertilizer and organic amendments are applied to meet the plants’ nutritional demands, however the effect of such practices on the associated rizospheric microbial communities are still unknown. Nitrogen plays an important role in agricultural production, and a great diversity of microorganisms regulates its transformation in the soil, affecting its availability for the plant. The aim of this study was to assess the structure of microbal[trm1]  communities related with the N cycle of S. tuberosum group phureja  rizospheric soil samples, with contrasting physical-chemical properties and fertilization strategy.  Few significant differences between the community composition at the phylum level were found, only Planctomycetes phylum was different between samples of different soil type and fertilization strategy. However, the analysis of nitrogen-associated functional groups made by ribotyping characterization, grouped soils in terms of such variables in a similar way to the physical-chemical properties. Major differences between soil samples were typified by higher percentages of the ribotypes from nitrite oxidation, nitrogen fixation and denitrification on organic amendment soils. Our results suggest that, the dominant rhizosphere microbial composition is very similar between soils, possibly as a result of population’s selection mediated by the rhizosphere effect. However, agricultural management practices in addition to edaphic properties of sampled areas, appear to affect some functional groups associated with the nitrogen cycling, due to differences found on soil’s physical-chemical properties, like the concentration of ammonium that seems to have an effect regulating the distribution and activity of nitrogen related functional groups in the S. tuberosum rhizosphere.